ANALISIS BAHAN AJAR KEBERAGAMAN SUKU BANGSA BUDAYA DALAM MEMBENTUK KARAKTER TOLERANSI DI SEKOLAH DASAR - Intan Kharismatun Nisya; Husna Farhana (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This research aims to ensure that the character of tolerance can be formed in students, so through the Pancasila and Citizenship Education subjects students can learn about the study of cultural diversity, the environment and community life which can be used as a forum for forming the character of tolerance in everyday life. This research method uses descriptive qualitative to explain real conditions as they are and the data obtained is in the form of sentences and other images. The data sources for this research are class IV A teachers, class IV B teachers and class IV A students. Based on the research results, it can be concluded that teaching materials for ethnic and cultural diversity are very important for forming students' tolerant character in understanding ethnic, cultural and religious differences through the character of tolerance that respects, respects, works together and does not differentiate between friends. However, there is still a lack of teaching materials that only focus on books, in this case there are some students who do not understand differences in ethnicity, culture and religion because the teacher does not pay attention when explaining because he feels bored only focusing on one teaching material. The lack of tolerance character of class IV A students can be seen by the students still chatting and playing when the teacher explains the material.